Reflexiones respecto a la construcción de conocimientos en el área de la enseñanza de las artes plásticas - Castro Bonilla, Julieta (2011)
The innovations produced day by day in the scientific, technological, environmental and social fields, among others, affect not only education but also teachers’ performance. In this context, education plays an important role in encouraging policies that can respond to the needs and interests of those are involved in this social context. This article intends to help the fine arts teacher to understand that as facilitator of the teaching learning process, his or her training practice must be based on theoretical referents that allow his or her students to go beyond the theoretical- critical analysis and thus reach substantial and attainable proposals which could be transferred to other contexts. Moreover, this teacher does not have to consider him/ herself the absolute owner of truth and knowledge. In order to generate important learning experiences for the students, s/he should consider interviewing theories such as constructivism, holism, multiple intelligences, pedagogy, psychology, epistemology and other didactic methods. The fine arts teacher is responsible for studying and researching rigorously these theories, as well as practicing a variety of artistic techniques regularly. The theories will ease the development of students’ learning abilities so that they assimilate information effectively, make decisions, solve problems and increase their creativity.